MARGINALIZATION OF FEMALE TEACHERS IN THE APPOINMENT OF HEADMASTERS OF PUBLIC SCHOOLS IN DENPASAR CITY - Citrawan, I Wayan (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2013)
Partiality between male and female teachers in regard to the appointment of the headmasters of public schools in Denpasar has taken place. This study was intended to understand the matters pertaining to the marginalization of female teachers in the appointment of the headmasters of public schools in Denpasar City.The data were obtained using the techniques of observation, in-depth interview, and documentation study. The data were descriptively, qualitatively, and interpretatively analyzed. The theories used were the theories of Feminism, Hegemony,Theory of Power/Knowledge, and Deconstruction. The results of the study were as follows. The government regulation was not optimally applied. The female teachers were considered having insufficient capability. They were still regarded as the second in the selection process, and they were assumed to be in the domestic domain; as a result, the access to their development was obstructed. The internal factors included competition and commitment and the external ones included patriarchal ideology, the government policy and less support from their colleagues and administrative staff at the schools where they work. The impacts of the marginalization of the female teachers were that they intended to improve themselves and to submit to their fate. The other impact was that they got disappointed and obstructed to realize gender impartiality. Philosophically, the marginalization of the female teachers meant that there was no gender partiality and self actualization.